Impact of improved upper endoscopy quality on detection of gastric precancerous lesions. Issue 3 (17th January 2023) - Manfredi, Guido; Pedaci, Marianna; Iiritano, Elena; Alicante, Saverio; Romeo, Samanta; Bertè, Roberto; Londoni, Claudio; Menozzi, Fernanda; Brambilla, Gianfranco; Pezzilli, Raffaele; Zullo, Angelo; Buscarini, Elisabetta
Abstract : Objective: Intestinal metaplasia (IM) is the point of no return in gastric carcinogenesis, and patients with extensive (antrum plus corpus) IM are at high risk of developing gastric cancer. We evaluated the impact of improved gastroscopy quality on the detection of gastric IM in an Italian area at high risk for gastric cancer. Methods: Data of consecutive patients with gastric biopsies according to the updated Sydney System observed in 2013, 2016 and 2019 resulting in IM diagnosis were retrieved. In the first period, endoscopy was performed with standard white light instruments. In the second period, preendoscopic gastric preparation was administered, and the examinations lasting at least 7 min with standard endoscopes were performed. In the third period, the latter procedure was followed, with virtual chromoendoscopy equipped instruments. The prevalence of IM in any gastric site and that of extensive IM were compared among the three periods. Results: Data of 3485 patients were available. The detection of IM in at least one gastric site increased from 29.9 to 33.6% and 34.5% (95% CI, 32.1–36.8) in the first, second and third period, respectively. The difference was statistically significant between the first and last ( P  = 0.02; OR, 1.24; 95% CI, 1.04–1.48) period. When considering extensive IM, the detection increased from 4.28 to 6.1% and 5.44%, although the difference failed to reach statistical significance ( P  = 0.076). Conclusion: Our data showed that implementation of a quality protocol increased the probability to detect IM in the stomach, allowing us to select patients deserving stricter follow-up.